Longer-Term Follow-Up of Kenyan Men Circumcised Using the ShangRing Device. - Paul J Feldblum (PLoS ONE, 2015)
To ascertain clinical sequelae, client satisfaction and sexual behavior 2+ years after male circumcision using the ShangRing device.We enrolled 199 men from the Kenya sites (Homa Bay district) participating in a 2012 study of the ShangRing device used in routine male circumcision services (N = 552). We enrolled men who had had the ShangRing placed successfully, and over-sampled men who had had an adverse event and/or were HIV-positive during the field study. In the present study, each participant was examined and interviewed by a study clinician, and penile photographs were taken to document longer-term cosmetic results and any abnormal findings.194 men were included in the analysis. The mean and median times between circumcision and the longer-term follow-up visit in this study were 31.8 and 32 months, respectively. Four men (2.1%) had signs/symptoms of a sexually transmitted infection (STI). Virtually all (99.5%) of the men were very satisfied with the appearance of their circumcised penis, and all would recommend a ShangRing circumcision to friends or family members. The most prevalent reported advantage of the circumcision was the ease of bathing and enhanced cleanliness of the penis (75.8%). 94.3% of the men did not cite a single negative feature of their circumcision. 87.5% of men reported more sexual pleasure post-MC, the most common reason being more prolonged intercourse. The majority of men (52.6%) reported one sexual partner post-MC, but more than a quarter of the men (28.1%) reported an increased number of partners post-MC. Less than half of the men (44.3%) reported using condoms half of the time or more, but the great majority of condom users stated that condom use was much easier post-MC, and 76.9% of users said they used condoms more after circumcision than before.This study supports the safety and acceptability of ShangRing male circumcision during 2-3 years of follow-up. It should allay worries that the ShangRing procedure could lead to delayed complications later than the observation period of most clinical studies.ClinicalTrials.gov NCT01567436.